Pengaruh Pemberian Kombinasi Short Wave Diathermy Dan Mc Kenzie Exercise Terhadap Penurunan Nyeri Pada Penderita LBP Myogenic Di RS Semen Gresik - Hana Thrisminarsih; Agung Endaryanto; Sartoyo Sartoyo; Angria Pradita (Jurnal Keperawatan Muhammadiyah, 2023)
Objective: To find out whether the administration of SWD and Mc Kenzie Exercise has an effect on reducing pain in patients with myiogenic low back paint conditions at Semen Gresik Hospital.Methods: This article uses pre and post test experiments conducted on 20 patients with low back pain at Semen Gresik Hospital. Strengthening exercises were carried out for 4 weeks with an intensity of 8 meetings (2 times a week).Results: SWD procedure and MC Kenzie exercise had a significant effect on reducing pain in patients with myogenic Low Back Pain (LBP) conditions at Semen Gresik Hospital with an average reduction in pain of 2,9. The initial value (pre-test) was 4,55 to 1,65 after receiving the SWD procedure and Mc Kenzie exercise (post-test) for 1 month (8 meetings).Â Conclusion: SWD procedure and MC Kenzie exercise had a significant effect on reducing pain intencity of 20 patients at Semen Gresik Hospital with Low Back Pain (LBP) Myiogenic as a respondent.